Project-Based Learning Evaluation trends in 21st Century Skills Development: bibliometrics and VoS Viewer: Tren Evaluasi Pembelajaran Berbasis Proyek dalam Pengembangan Keterampilan Abad ke-21: bibliometrik dan VoS Viewer - Alvira Pranata; Tri Syamsijulianto (Journal of Innovative and Creativity, 2025)
This study aims to evaluate research trends related to Project-Based Learning (PjBL) in 21st-century skills development through a bibliometric approach. 21st-century skills, such as critical thinking, collaboration, communication, and creativity, are a major focus in modern education, and PjBL is seen as a relevant pedagogical approach to cultivating those skills. However, systematic mapping of research trends and scientific collaboration in this field is still limited. This study uses a bibliometric method by analyzing 174 articles indexed by Sinta and Scopus from 2015 to 2025, which contain keywords related to "Project-Based Learning" and "21st Century Skills". Data was analyzed using VOSviewer software to visualize collaboration networks, keywords, and the distribution of authors and institutions. The results of the analysis show that there has been a significant increase in publications related to PjBL and 21st-century skills in the last five years. The main keyword clusters found include: project-based learning, 21st century skills, collaborative learning, STEM education, and critical thinking. The United States, Indonesia, and Spain are listed as the countries with the highest contributions in publications. Bibliometric visualization also shows that the topic of PjBL in the context of 21st-century skills is increasingly shifting towards strengthening the integration of digital technology and cross-disciplinary approaches. This study provides a comprehensive overview of the direction of research development and the potential for cross-border collaboration and suggests the need for a more structured evaluative approach in the implementation of PjBL in various educational contexts.